2016
DOI: 10.1007/s10984-015-9202-5
|View full text |Cite
|
Sign up to set email alerts
|

Learning support and academic achievement among Malaysian adolescents: the mediating role of student engagement

Abstract: The aim of this study was to examine the associations between learning support, student engagement and academic achievement among adolescents. We also examined the extent to which affective, behavioural and cognitive engagement play a mediating role in students' perceived learning support from parents, teachers and peers, and contribute to their academic achievement. Malaysian adolescents (aged 12-17 years, N = 2359) completed a selfadministered questionnaire based on an adapted version of the Student Engageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
76
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 55 publications
11
76
0
14
Order By: Relevance
“…So, it's easy to do with a friend, because then you like have to do it. (Interviewee 13) This is consistent with research reported by Jelas, Azman, Zulnaidi and Ahmad (2016), which identified the perception that there are friends whom one can turn to and share experiences with as a positive factor for cognitive engagement and academic achievement.…”
Section: Being Part Of a Groupsupporting
confidence: 84%
“…So, it's easy to do with a friend, because then you like have to do it. (Interviewee 13) This is consistent with research reported by Jelas, Azman, Zulnaidi and Ahmad (2016), which identified the perception that there are friends whom one can turn to and share experiences with as a positive factor for cognitive engagement and academic achievement.…”
Section: Being Part Of a Groupsupporting
confidence: 84%
“…should also be considered. Jelas et al (2016) examined adolescents’ perceptions of learning supports from parents, teachers and peers simultaneously, and their effect on student engagement. The data analysis was conducted by structural equation modeling.…”
Section: Pre-actional Decisional Phasementioning
confidence: 99%
“…Empirical studies have focused on families and have proven the significant role of parents as contributors to school engagement and students’ performance at school (Bempechat and Shernoff, 2012). Family members who provide academic (e.g., assisting with homework) or motivational (e.g., recognizing effort and enhancing progress) supports help improve students’ academic performance (Jelas et al, 2016). Moreover, parents’ support and involvement may influence the way that their children perceive their own abilities or the way they value the subjects (Rodríguez et al, 2017).…”
Section: Pre-actional Decisional Phasementioning
confidence: 99%
“…University student engagement has become a construct of interest in research (Kahn, 2014). Previous studies have shown that it is directly linked to academic success (Jelas et al, 2016). Hence, it is essential to understand what leads students to engage in their academic activities.…”
Section: Introductionmentioning
confidence: 99%